Edukacja outdoor w praktykach studenckich a rzeczywistość - Roszak, Bożena (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
In this paper an attempt to examine students internships from the perspective of outdoor education and to point out the benefits it brings in the process of education and teaching is made. The analysis also includes the following aspects of the model of learning: comfort, tension, panic, which are conductive to acquiring soft skills during outdoor activities. Outdoor activities require from teachers to use competences that are not disclosed in formal school education and therefore it is also important to analyse the competences that are desired in a student, apprentice and a teacher, who offer outdoor activities to their students.
Keywords: education; outdoor; student internship; teacher’s competency